Surgically Induced Astigmatism Comparison between Forceps and Injector Delivery System for Foldable IOL in Phacoemulsification - Khalid Waheed, Tahir Mahmood, Nasrullah Khan, Atif Mansoor Ahmed (Pakistan Journal of Ophthalmology, 2011)
Purpose: To compare surgically induced astigmatism between injector and forceps delivery system for intraocular lens implantation in phacoemulsification. Material and Methods: This Quasi experimental study was carried out in Ophthalmology Department, Shaikh Zayed Hospital, Lahore. One hundred consecutive cataract patients were operated upon by phacoemulsification with acrylic foldable IOL implantation. Patients were randomly divided into two groups i.e. group I, injector delivery system and group II forceps delivery system for IOL implantation. Preoperative and postoperative keratometric reading of the patients were taken by Javal-Schiotz keratometer. All patients were followed for 8 weeks. Surgically induced astigmatism was calculated by vector method. Results: The mean preoperative astigmatism K1 in group I was 0.545 D (±0.538) while in group II was 0.615 D (±0.587). The mean postoperative astigmatism K3 in group I was 0.86 D (±0.580) and in group II was 0.785 D (±0.670). The mean surgically induced astigmatism in group I was 0.998 D (±0.532) and 1.064 D (±0.757) in group II. The difference in surgically induced astigmatism K2 in both groups was 0.066 D, not significant (P=0.625). Conclusion: Both injector and forceps delivery systems of IOL were safe and equally acceptable with insignificant difference in surgically induced astigmatism.